PENATALAKSANAAN FISIOTERAPI PADA HEMIPLEGI SINISTRA ET CAUSA STROKE WHITE MATTER NON- HEMORAGIK DENGAN NEW BOBATH CONCEPT DI RS HERMINA JATINEGARA - Cicilia Febriani Hayuningrum; Ayu Wulandari; Andrew Wijaya Saputra; Agus Wiyono (Jurnal Kesehatan Abdurrahman, 2026)
Non-hemorrhagic white matter stroke in the cerebral cortex can result in ipsilateral symptoms such as sensory and motor impairments, loss of balance, cognitive decline, and reduced mobility in both upper and lower extremities. These deficits significantly hinder the individual's ability to perform effective postural control, leading to difficulties in maintaining body position and directing movement. Consequently, patients with white matter lesions often experience functional movement limitations and exhibit uncoordinated or purposeless motor activities. This study aims to investigate the impact of physiotherapy intervention using the New Bobath Concept in a case of hemiplegia caused by non-hemorrhagic white matter stroke, focusing on improvements in postural control, body stability, gait pattern, and upper extremity functional abilities, particularly in reaching and grasping tasks. This study employed a case study design involving a four-week physiotherapy intervention based on the New Bobath Concept. Following five therapy sessions, notable improvements were observed, including enhanced body posture, improved postural control, increased weight-bearing on the left (affected) side, correction of the circumduction gait pattern, and improved upper limb functional performance in reaching and grasping tasks. Physiotherapy intervention using the New Bobath Concept demonstrated beneficial effects in enhancing postural alignment, improving postural control, facilitating weight-bearing on the affected side, correcting gait abnormalities, and increasing upper extremity function in a patient with hemiplegia due to non-hemorrhagic white matter stroke.